(untitled) (Research, Society and Development, 2021)
Introduction: Mechanical-associated pneumonia (VAP) is identified as an implicit cause of mortality in patients hospitalized in Intensive Care Units (ICU). Pseudomonas aeruginosa is an important VAP agent that has multiple resistance to antimicrobials, being considered a serious public health problem. In this context, polymyxin antimicrobials are considered the best therapeutic option for the treatment of these diseases. Objective: To analyze the susceptibility profile and mechanisms of resistance to polymyxins in granting of P. aeruginosa causing VAP. Methods: A systematic review was conducted according to the Cochrane Handbook and the research and analysis of the articles followed the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Results: 22 articles were included and most were published from 2015, highlighting the year 2017 (22.7%), especially in Asian countries. 1,490 P. aeruginosa isolates recovered from ICU patients (16 pediatric ICUs) were analyzed. The susceptibility profile of the isolates to polymyxin B and/or colistin was determined by microdilution (40.9%) and Kirby-Bauer methods. 2.57% of the P. aeruginosa isolates were resistant to colistin and a lower resistance (1.87%) was observed for polymyxin B. Conclusion: No study investigated the presence of the plasmid gene encoding resistance to polymyxins (mcr) among the isolates, although this gene has already been reported in this species. Therefore, further research is needed to monitor the resistance and resistance mechanisms of P. aeruginosa to polymyxins, in order to preserve the therapeutic efficacy of this class of antibiotic.